2009
DOI: 10.22358/jafs/66378/2009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of live and autoclaved yeast cultures on ruminal fermentation <i>in vitro</i>

Abstract: The objective of this study is to determine whether a yeast culture of Saccharomyces cerevisiae has an effect on parameters of ruminal fermentation and whether the potential positive effects of yeast culture are associated with the yeast's viability. For this purpose, live and autoclaved yeast cultures were tested simultaneously in the rumen simulation technique (Rusitec). Each fermentation vessel received daily 9 g of a basal diet consisting 5 g meadow hay and 4 g pelleted concentrate.Yeast preparations (1.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
35
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 19 publications
8
35
4
2
Order By: Relevance
“…The effects observed on NH 3 -N with both ADY and KDY are consistent with previous in vitro studies using either ADY (Miller-Webster et al, 2002) or both ADY and KDY (Oeztuerk, 2009). However, most of the previous animal studies have shown either no effects (Newbold et al, 1996;Yoon and Stern, 1996;Thrune et al, 2009) or reduced ruminal NH 3 -N concentration (Erasmus et al, 1992;Lascano and Heinrichs, 2007) in response to yeast supplementation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The effects observed on NH 3 -N with both ADY and KDY are consistent with previous in vitro studies using either ADY (Miller-Webster et al, 2002) or both ADY and KDY (Oeztuerk, 2009). However, most of the previous animal studies have shown either no effects (Newbold et al, 1996;Yoon and Stern, 1996;Thrune et al, 2009) or reduced ruminal NH 3 -N concentration (Erasmus et al, 1992;Lascano and Heinrichs, 2007) in response to yeast supplementation.…”
Section: Discussionsupporting
confidence: 89%
“…However, most of the previous animal studies have shown either no effects (Newbold et al, 1996;Yoon and Stern, 1996;Thrune et al, 2009) or reduced ruminal NH 3 -N concentration (Erasmus et al, 1992;Lascano and Heinrichs, 2007) in response to yeast supplementation. The effects on NH 3 -N in various in vitro studies (Miller-Webster et al, 2002;Oeztuerk, 2009) were attributed to the microbial degradation of yeast cells because of their high protein content. However, this explanation might not be pertinent to the present study because the level of yeast supplementation was lower (0.35 mg/g of DMI) as compared to previous in vitro studies (Miller-Webster et al, 2002;Oeztuerk, 2009) and microbial degradation of yeast cells supplemented at lower levels would not increase NH 3 -N concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, propionate is energetically more efficient because its production is in indirect competition with methanogens for metabolic hydrogen (Hegarty 1999). The effects observed on NH 3 -N with hydrolysed yeast products are consistent with previous in vitro and in vivo experiments using inactivated yeast products (Oeztuerk et al 2005;Oeztuerk 2009;Vyas et al 2014). The increase in NH 3 -N concentration, especially at 0.75 g, can be associated with the microbial degradation of yeast products because of their high protein content.…”
Section: Discussionsupporting
confidence: 89%
“…Yeast derivatives were also effective in the stimulation of rumen fermentation, and are considered to have a prebiotic effect . Unlike LY, the main role of YD is as a nutritional provider for microbes to stimulate ruminal fermentation.…”
Section: Discussionmentioning
confidence: 99%